Teaching a foreign language for professional purposes: overview of the experience of Kazakhstani teachers and methodologists (Journal of Educational Sciences, 2023)
The study of problems of teaching a foreign language does not lose its relevance among Kazakhstanresearchers in connection with the pace of development of the modern labor market. The need toparticipate in international scientific conferences, to study and analyze the results of scientific researchpresented in foreign sources, to communicate and exchange experiences with foreign colleagues havebecome part of today’s reality for the professional development of specialists in all areas of human activity.Representatives of all kinds of specializations face these professionally significant situations, wherethe use of a foreign language is a self-evident condition for achieving profession-related goals and meetingprofessional needs. In this regard, this paper examines the problem of teaching a foreign languagefor professional purposes to students of non-linguistic universities in Kazakhstan. In this study, generaltheoretical methods of research were applied: analysis, synthesis, generalization. In the course of thisresearch, the following results were achieved: (а) theoretical review and analysis of professional foreignlanguage training models proposed by Kazakhstani researchers for technical, financial and economic,agroeconomic profiles were carried out; (b) the principles that most closely determine the success of theprocess of teaching a foreign language for professional purposes have been identified and systematized;(c) a basic set of tasks and exercises to improve the effectiveness of the process of learning a foreignlanguage for professional purposes was proposed based on the synthesis of the experience of domesticresearchers.Key words: foreign language education, foreign language teaching, English for professional purposes,professional communication.